(untitled) (International Journal of Nursing Education, 2022)
At present scenario COVID infection creates a pandemic and cruel deadly situation through worldwide. First case of Corona virus infection reported in Wuhan City of China in December 2019.Beginging from normal fever & common cold it becomes severe with the symptoms of breathing difficulty, persistent fever, loss of taste & smell etc. It travels through air from human to human as a form of droplet infection. So, to check and increases the knowledge regarding prevention of corona virus among staff nurses working in AH & RC, B.G Nagara, Karnataka; I have done one video assisted teaching (VAT) session. Among total 60 staff nurse I have divided them into two groups as follows: 40 members in Experimental group & 20 members in Control group. The data collection done from 01-10-2021 to 11-10-2021 in AH & RC, B. G Nagara. After data analysing found that in the pre-test level of knowledge 80% Poor, 15% Average, 5% Good knowledge in control group and 75% Poor, 20% Average, 5% Good knowledge experimental group. The above posttest reveals that the percentage distribution of level of knowledge 60% Poor, 30% Average, 10% Good knowledge in control group and Average 7.5% ,62.5% Good & 30% having very good knowledge in experimental group.The results show that gained knowledge by the effectiveness of video assisted teaching in experimental group is 44.43%.